Drying characteristics of cucumber slices using hot air and sun drying - Nooremylia Abdullah (2011)
The main purpose of this study was to study the characteristic of drying cucumber (Cucumis sativus) slices using hot air and comparing with sun drying. The factor investigated in hot air drying was air temperature with minimum temperature of 60 °C and maximum temperature of 90°C. The sample thickness was also investigated with minimum thickness of 0.5 cm and maximum thickness of 1 cm. In this study, all data was analyzed using statistical software SAS. The type of design that was used is response surface design. The number of run of this experiment is thirteen runs. From this study, it was found that cucumber slices would dry perfectly within 180, 345 and 465 min to achieve the commercial moisture content of cucumber slices under these drying conditions for hot air drying. Whereas, sun drying took 660 to 780 min. The higher the temperature, the shorter the drying time. It was also observed that the suitable drying time for 0.5 cm thick material was 570, 330 and 195 min for drying temperature of 60, 75 and 90 °C, respectively. The effect of drying air temperature and slice thickness on the drying characteristics and quality parameter of the dried cucumber slices were also determined. From data optimization using statistical software SAS, the optimum condition that recommended for hot air drying is with air temperature of 60 and 75 °C with slice thickness of 0.5 cm.